Application of Blockchain Technology in the Governance of Executive Corruption in Context of National Audit - Jie Wang; Xiaomei Wang*; Hanxiu Cheng (Tehnički Vjesnik, 2020)
To reduce the impact of hidden corruption of the state-owned enterprise executives, first, this paper uses the difference-in-difference (DD) analysis method to build the DD model in the context of national audit. Second, the study analyzes the impact of the operating performance of the state-owned enterprises on the enterprise value. Third, it discusses the impact of the executive power of the state-owned enterprises on the hidden corruption, and uses blockchain technology with decentralization and high transparency, and information not be tampered with to analyze the degree of information transparency in state-owned enterprises, thereby enhancing the existing audit mode and improving the audit efficiency, and further predicting the trend of hidden corruption for finding the characteristics of corruption as early as possible, and timely governing the corruption behaviors. The research results show that the greater the power of state-owned enterprise executives is, the lower the transparency of information is, the less sound the supervision mechanism is, and the easier the hidden corruption of state-owned enterprise executives will breed. Only by using blockchain technology to enhance the audit mode, ensure data integrity, improve audit efficiency, and decrease audit risk, can the corruption of the executives of state-owned enterprises be effectively curbed.